Perguntas em terapia comunitária integrativa: um estudo em uma organização - Vicente, Eurídice Bergamaschi (2012)
The objective of the study was to hold an intervention-study in order to understand the role of the questions posed by the therapist in the Contextualization and Sharing of Local Knowledge stages of a Conversational Round held in an Organization. The conversational dialogic process occurring during a Round is kept moving by questions, which the therapist uses with intention in order to obtain more information, establish relations between facts, link events and guide the conversational flow. To understand the role of questions in Conversational Rounds within the setting of an Organization may help in reflection upon the application of ICT Integrative Community Therapy in this context. This intervention-study was carried out with 49 employees from the industrial area of a Sugar and Ethanol Organization in the State of São Paulo, and involved a Round of Conversation. The protagonist was also interviewed. The conversational round model proposed by Adalberto Barreto was followed, with its six stages: Welcoming, Select a Theme, Contextualization, Sharing of local knowledge, Aggregation rituals and Evaluation. The material collected from the narratives during Contextualization, Sharing of local knowledge and interview was analyzed in order to classify the questions according to Karl Tomm's model: Lineal, Strategic, Circular and Reflexive questions. The new-paradigmatic theoretical assumptions of Systemic Thinking, Narrative Practice and Collaborative Posture were followed as well as Foucault's vision of power and knowledge. As results we observed that Lineal Questions were asked in order to obtain factual information or with a confirmatory goal after the Editorial. Strategic Questions enabled a broader scenario to be set; the participant's perception to be reinforced, reorientation of thinking to be proposed. Circular Questions enabled more information to be obtained and the subjects presented to be explored, and extended participants' perceptions to new spaces of feeling, acting and perceiving; and to an understanding of how events connect. Reflexive Questions allowed disruption of the existing circular process; the expression of personal and group values and beliefs; the protagonist to feel encouraged to confront an issue and seek his own resources as well as experience a given situation in the field of feeling. Although the importance of the role of questions in Conversational Rounds is obvious, with the type of question defined after the answer, one may state that in the Organizational context the Panopticon is clearly present. Its linking strength between the power and the quotidian in a group may prevent a process of normalized subjectivization from failing to occur, through coercion. It is through power and practices of freedom that the production of subjectivities takes place, and this was observed in the present study